Organized by Norrkoping Air, affiliated with Linkoping university and the Museum of Forgetting, Sweden - (:unkn) unknown (My University, 2026)
Experimental Storytelling, Norrköping City Museum Lecture and Seminar In the Frame of Orphaned Images Exhibition Organized by Norrkoping Air, affiliated with Linkoping university and the Museum of Forgetting, Sweden Sweden